Screening lentil (Lens culinaris) RIL population for high yield and aluminium toxicity tolerance under acidic field and hydroponic conditions - MAHANTA, MAYURAKSHEE; KONJENGBAM, NOREN SINGH; PHEIRIM, REGINAH; LYNGDOH, ANDREAN ALLWIN (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried out during winter (rabi) season of 2020–21 at two locations namely the experimental field of College of Post Graduate Studies in Agricultural Sciences (Central Agricultural University, Imphal, Manipur), Umiam, Meghalaya and Agro-forestry experimental plot of ICAR-North-Eastern Hill Region, Meghalaya followed by hydroponics screening during winter (rabi) season of 2021–22. The experiments involved screening of a recombinant inbred line (RIL) population of lentil (Lens culinaris Medik) obtained from a cross between BM-4 (Al sensitive parent) and L-4602 (Al tolerant parent) for high yield and Al (aluminium) toxicity tolerance through evaluation in the acidic field conditions, character association studies and root growth studies under hydroponics having toxic Al concentration of 148 µM. Highly significant variance due to genotypes revealed presence of sufficient variability for all the traits except number of seeds/pod (SP). Among the characters, high Hbs2 associated with high GA% were recorded in number of primary branches/plant (NB), plant height (PH) and 100-seed weight (SW). Path analysis revealed that, number of pods/plant (PP) (0.840) had the greatest direct effects in influencing seed yield/plant (SYPP), followed by biological yield/plant (BYPP) (0.795), number of seeds/pod (SP) (0.474), number of primary branches/plant (NB) (0.309) and harvest index (HI) (0.307). Correlation studies among root and shoot parameters under hydroponic studies revealed significant correlation between root dry weight (RDW) and shoot dry weight (SDW); shoot fresh weight (SFW) and root fresh weight (RFW); total root length (TRL) and surface area (SA); and haematoxylin stain score (STNS) and root regrowth (RRG). Based on mean performance of SYPP and attributing traits, combined with root growth studies under hydroponics, the high yielding and Al toxicity tolerant genotypes identified were LRIL-37, LRIL-22, LRIL-68, LRIL-96 and LRIL-97. In addition to serving as parents in hybridization programmes, these genotypes may undergo additional evaluation in multiple environments prior to final release in an effort to enhance performance.